Development potential and technical strategy of continental shale oil in China - Suyun HU; Wenzhi ZHAO; Lianhua HOU; Zhi YANG; Rukai ZHU; Songtao WU; Bin BAI; Xu JIN (Petroleum Exploration and Development, 2020)
Continental shale oil is a general term for liquid hydrocarbons and many kinds of organic matter in continental organic-rich shale series with vitrinite reflectance of more than 0.5% at buried depth of more than 300 m, and is an important type of source-rock oil and gas. Based on the evolution model of oil generation and expulsion in organic-rich shale series controlled by maturity, continental shale oil is divided into two types: medium-high maturity and medium-low maturity. (1) The continental shale series in China develop high-quality source rocks of freshwater and saltwater lacustrine facies, as well as multiple types of reservoirs, including clastic rocks, carbonate rocks, diamictite, tuff and shale, forming a number of “sweet sections” and “sweet areas” of continuous distribution inside or near source rocks, which have large scale resources. (2) Experimental analysis of organic rich shale samples shows that the shale samples with wavy and horizontal beddings have good storage conditions, and the horizontal permeability of shale is tens to hundreds of times of its vertical permeability, which is conducive to the lateral migration and accumulation of shale oil in the source rocks. (3) After evaluation, the geological resources of medium-high maturity shale oil are about 10 billion tons, which can be effectively developed by horizontal drilling and volumetric fracturing, and will be a practical field of oil exploration in recent years. Shale oil with medium and low maturity has huge resource potential, and technological recoverable resources of (70–90) billion tons, making it a strategic alternative resource of oil industry. However, economic development of this type of shale oil needs in-situ conversion technology breakthroughs. Continental shale oil is an inevitable choice in the process of Chinese continental petroleum exploration from “outside source” to “inside source”. Making breakthroughs in the core technologies such as “sweet area” evaluation and optimization, horizontal well volume fracturing and in-situ conversion technology and equipment is the key to realizing scale development of continental shale oil economically.